Potential for Further Mismanagement of Fever During COVID-19 Pandemic: Possible Causes and Impacts - Singh, Samer; Kishore, Dhiraj; Singh, Rakesh K. (Frontiers in Medicine, 2022)
Fever remains an integral part of acute infectious diseases management, especially for those without effective therapeutics, but the widespread myths about ‘fevers’ and presence of confusing guidelines from different agencies, which have heightened during the COVID-19 pandemic and are open to alternate interpretation, could deny whole populations the benefits of fever. Guidelines suggesting antipyresis for 37.8-39oC fever are concerning as 39oC boosts protective heat-shock and immune response (humoral, cell-mediated, nutritional) whereas ≥40oC initiates/enhances the antiviral responses and restricts high-temperature adapted pathogens, e.g., SARS-CoV-2, strains of influenza, measles. Urgent attention is accordingly needed to address the situation because of the potential public health consequences of the existence of conflicting guidelines in the public domain. We have in this article attempted to restate the benefits of fever in disease resolution, dispel myths and underline the need for alignment of national treatment guidelines with that of the WHO, to promote appropriate practices and reduce the morbidity and mortality from infectious diseases including COVID-19.